A brief history of analytic philosophy : from Russell to Rawls - Schwartz, Steve. 1944- (Chichester : Wiley-Blackwell, 2012)
"A Brief History of Analytic Philosophy: From Russell to Rawls presents a comprehensive overview of the historical development of all major aspects of analytic philosophy, the dominant Anglo-American philosophical tradition in the twentieth century. Features coverage of all the major subject areas and figures in analytic philosophy - including Wittgenstein, Bertrand Russell, G.E. Moore, Gottlob Frege, Carnap, Quine, Davidson, Kripke, Putnam, and many others Contains explanatory background material to help make clear technical philosophical concepts Includes listings of suggested further readings Written in a clear, direct style that presupposes little previous knowledge of philosophy "--
Machine generated contents note: Preface Introduction Chapter 1: Russell and Moore Chapter 2: Wittgenstein, The Vienna Circle, and Logical Positivism Chapter 3: Responses to Logical Positivism, Quine, Kuhn, and American Pragmatism Chapter 4: Ordinary Language Philosophy and Later Wittgenstein Chapter 5: Responses to Ordinary Language Philosophy- Logic, Language, and Mind Chapter 6: The Rebirth of Metaphysics Chapter 7: Naming, Necessity, and Natural Kinds- Kripke, Putman, and Donnellan Chapter 8: Ethics and Metaethics in the Analytic Tradition Epilogue: Analytic Philosophy Today and Tomorrow.
Includes bibliographical references (p. 327-336) and index.
Keywords: Analysis (Philosophy) -- History; PHILOSOPHY / History & Surveys / General